Pengaruh Harga Minyak dan Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia - Resi Yunita; Yeniwati Yeniwati (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze the effect of world oil prices and inflation on economic growth in Indonesia. The type of data used is time series data from 1987 to 2020 taken from FRED Economic Data, the World Bank and the Central Statistics Agency. This type of research is descriptive and associative research. The data analysis used is descriptive analysis and inductive analysis. Stationarity test is one of the tests used in inductive analysis; (2) Cointegration Test; (3) Multiple Linear Regression Test and Error Correction Model (ECM); (4) Classical Assumption Test; (5) T test and F test. The results of this study reveal that: (1) world oil prices (X1) have an insignificant negative effect on economic growth (Y1) in Indonesia in the long term and in the short term world oil prices (X1) have an insignificant negative effect on economic growth (Y1) in the long term. positive and significant to economic growth (Y1) in Indonesia; (2) inflation (X2) has an insignificant negative effect on economic growth (Y1) in Indonesia in the long term while in the short term inflation (X2) has an insignificant negative effect on economic growth (Y1) in Indonesia.